The Lexicographical Contribution of Hermilio Valdizán: Analysis of the “Diccionario de Medicina Peruana” (1923-1961) - Molina Sangüesa, Itziar (2024)
The objective of this paper is to present an unknown text in the fields of philology and the history of science: the Diccionario de medicina peruana (Dictionary of Peruvian Medicine), by Hermilio Valdizán (1923-1961). To this end, we analyze the macrostructure, microstructure and iconostructure of the nine volumes that constitute this monumental contribution to the historical, anthropological and ethnographic studies of the pre-Hispanic and colonial culture of Peru, to which Valdizán dedicated more than two decades of tireless documentary and compilation work. We offer a study of the lexical units included in this lexicographical repertoire, as well as the areas of specialization to which the word list compiled by Valdizán belongs, the lexicographical sources that he used for the preparation of his work and the presence of the indigenous element. This will be accompanied by a review of the biobibliographical, encyclopedic and linguistic contributions preserved in this dictionary, which is revealed as a fundamental piece to understand and (re)construct the medical history of Peru